2021
DOI: 10.4149/neo_2020_200502n480
|View full text |Cite
|
Sign up to set email alerts
|

miR-877-5p antagonizes the promoting effect of SP on the gastric cancer progression

Abstract: Gastric cancer is one of the four major tumors in the world and the second leading cause of cancer-related death. It was reported that Substance P (SP), as an oncogenic factor, could regulate the expression of miRNAs in gastric cancer progression. Here, we focused on the role of miR-877-5p in gastric cancer development and the miR-877-5p involvement in the SP-mediated gastric cancer development. The mRNA expression level and cell proliferation were assessed by quantitative real-time PCR and cell counting kit-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…At the functional level, some studies have shown that miR-877 promotes cell proliferation and invasion and induces cell apoptosis in many cancers. [ 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 ] The study collected prove to support the molecular mechanism and clinical conspicuousness of miR-877 in several cancers.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…At the functional level, some studies have shown that miR-877 promotes cell proliferation and invasion and induces cell apoptosis in many cancers. [ 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 ] The study collected prove to support the molecular mechanism and clinical conspicuousness of miR-877 in several cancers.…”
Section: Introductionmentioning
confidence: 73%
“…FOXM1 is known to play a key role in cell cycle progression where endogenous FOXM1 expression peaks at S and G2/M phases. Guo et al .,[ 23 ] (2020) verified miR-877-5p capability of targeting FOXM1 and negative regulation of its expression. Another study showed the ability of miR-877-5p for negative regulation of the GC progression through suppressing the rapid growth or proliferation of the cells and elevating apoptosis that may be followed by greater cleaved caspase-3 and caspase-9, as well as level of Bax protein and lower levels of Bcl-2.…”
Section: Hanges MI R-877 In D I...mentioning
confidence: 98%
See 1 more Smart Citation
“…We further examined the main hub Treg-related miRNAs (hsa-miR-877 and hsa-miR-137), which we showed were independent indicators of poor outcome. Hsa-miR-877 was found to be overexpressed in gastric cancer, and also antagonized the promoting effect of Substance P in the occurrence and progression of gastric cancer, suggesting that miR-877-5p could be a potential drug target [47] . Further, miR-877-5 has been reported to participate in gene regulation of competing endogenous RNA (ceRNA) mechanisms in multiple tumors, including cervical cancer, malignant gliomas, and non-small-cell lung cancer [48][49][50] .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the dysregulation of miRNA expression in human cancers through various mechanisms (10,11). miR-877-5p has been proved to a tumor suppressor that is involved in the development of several types of cancer, including hepatocellular carcinoma (HCC) (12), non-small cell lung cancer (NSCLC) (13), gastric cancer (14) and cervical cancer (15). miR-877-5p also functions to constrain the proliferative capacity of GBM cells (16).…”
Section: Introductionmentioning
confidence: 99%